Incorporating mathematical thinking in addition and subtraction of fraction: real issues and challenges - Khalid, Madihah (2007)
Since the introduction of the new primary mathematics curriculum in Brunei starting January 2006, more teachers of elementary schools are seeking a suitable way of incorporating mathematical thinking in each mathematics lesson that they teach. For this particular purpose, teachers were introduced to lesson study and it is hoped that with the guidance and support given by the team involved, teachers would build their confidence and make mathematical thinking a regular feature of their lessons. There are still many problems that the teachers face such as students not used to explaining their thoughts in class and some insisting on using certain procedures that they had learned before, without being able to explain how and why the procedure works. This paper will relate a classroom case and look at the real issues and challenges that Bruneian teachers faced in incorporating mathematical thinking when teaching of the topic on addition and subtraction of fractions.